FORMULATION DEVELOPMENT OF SAXAGLIPTINE MICROPARTICULATED DRUG DELIVERY SYSTEM FOR ENHANCING BIOAVAILABILITY AND STABILITY - Gyan Singh; (Dr.) Satish Kumar Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study investigates the design, development, and evaluation of sustained-release Saxagliptin microparticles. This approach facilitated an assessment of the concentration of coating material influenced the drug release rate. The solvent evaporation method proved effective in producing discrete, spherical microparticles characterized by good flowability and minimal stickiness. a few formulation techniques and analytical methods for Saxagliptin have been reported15-21, Therefore, this investigation seeks to design and develop novel microparticles of Saxagliptin aimed at treating diabetes22. This approach focuses on creating a controlled release formulation using a lower drug dose, thereby aiming to achieve consistent plasma drug concentrations. This may lead to enhanced patient compliance due to reduced dosing frequency, improved therapeutic efficacy, and minimized side effects resulting from a more controlled drug release profile. This study aims to develop a microparticle-based drug delivery system for Saxagliptin, its short biological half-life of approximately 3.1 hours necessitates frequent dosing (twice daily), which can contribute to non-adherence. Currently available in conventional tablet forms (2.5-5 mg/day), controlled release formulations present a promising solution. microparticles can encapsulate active ingredients, protecting them from degradation and facilitating their transport to specific sites within the body13. Their unique size and surface characteristics also allow for functionalization, enabling enhanced interaction with biological systems and improved efficacy in medical applications14.